The open ontology and information society - Naidoo, Meshandren (Frontiers in Genetics, 2024)
IInformation as the most elusive subject, is central to all forms of thought, governance, economic structure, science, and society. Regulation of information, especially within the healthcare field, is proving to be a difficult task globally, given the lack of a qualitative framework and understanding of the concept and properties of information (or data) itself. The presentation of overall qualitative framework, comprising of a qualitative analysis of information, data and knowledge will be valuable and great assistance in delineating regulatory, ethical, and strategic trajectories. Moreso, this framework provides insights (and answers) regarding: (1) data privacy and protection; (2) delineations between information, data and knowledge, based on the important notion of trust; (3) a structured approach to establishing the necessary conditions for an open society and system, and the maintenance of said openness, based on the work of Karl Popper and Georg Wilhelm Friedrich Hegel; (4) an active agent approach which promotes autonomy, freedom, and protects the open society; and (5) a data governance mechanism, based on the work of Friedrich Hayek, which structures the current legal-ethical-financial and social society. This is insightful for questions relating to extent of rights and duties, the extent of biological bodies and freedom, and the structure of relations in distributed networked systems. There is great value offered in this framework, and more-so, it provides critical insights and thoughts about (and uncover the interplay between) academic culture, politics, science, society, and societal decay. Note, that keeping in line with the ideas expressed in this manuscript, such as incorporation of personal experience (thus mending the Kantian and Cartesian gap) a first person perspective will be used, where relevant.